New leaf-mining Nepticulidae (Lepidoptera): potential pests of aromatic Lamiaceae plants from equatorial Andes - Stonis, Jonas R.; Diškus, Arūnas; Fernández-Alonso, José L.; Remeikis, Andrius; Solis, M. Alma (Zootaxa, 2021)
Members of the Lamiaceae, or mint family, are used worldwide for medicinal, culinary and/or magical-religious purposes, as well as in pesticides and as ornamental plants. Very little is known about nepticulids, or pygmy moths, as leaf miners of Lamiaceae, but they may be an important component of South American diversity and potential pests of economically-important species of the mint family. In this paper, four new species of leaf-mining Nepticulidae are described from the equatorial Andes of Ecuador: S. mentholica Diškus & Stonis, sp. nov., Stigmella aromatica Diškus & Stonis, sp. nov., S. odora Diškus & Stonis, sp. nov., feeding on Minthostachys mollis (Benth.) Griseb., and S. tomentosella Diškus & Stonis, sp. nov., feeding on Clinopodium tomentosum (Kunth) Govaerts. It is hypothesized that host-plant distribution ranges can provide clues to potential distribution ranges of these newly discovered, trophically specialized leaf miners. The leaf mines, adults, and the genitalia of the new species are illustrated with photographs.